المناعة النفسية وعلاقتها بالقلق وتوهم المرض المترتب على جائحة فيروس كرونا المستجد Covid-19 لعينة من طلاب الجامعة - الليثي، أحمد حسن محمد (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2020)
هدف البحث الحالي إلى الكشف عن العلاقة الارتباطية بين المناعة النفسية وكل من القلق وتوهم المرض لعينة من طلاب الجامعة، تكونت عينة البحث من (465) طالبا من بعض الجامعات المصرية تراوحت أعمارهم بين (18-22) عام بمتوسط عمري قدره (20.8) عام، وقد انقسموا إلى (٢٩٦) من الإناث، (١٦٩) من الذكور وقد أظهرت النتائج وجود علاقة عكسية دالة إحصائيا بين المناعة النفسية بأبعادها (التفكير الإيجابي، الثقة بالنفس، المواجهة الإيجابية، المرونة النفسية، تنظيم الذات، الضبط الانفعالي) وكل من القلق وتوهم المرض لعينة البحث من طلاب الجامعة، كما أظهرت النتائج وجود فروق دالة إحصائيا في القلق وتوهم المرض تعزى للنوع (ذكور-إناث) تجاه الإناث، ولم تتضح فروق دالة إحصائيا في القلق وتوهم المرض طلاب بين طلاب المناطق الريفية والحضرية، كما يستخلص الباحث من نتائج البحث الحالي أهمية تنمية المناعة النفسية لدعمه في مواقف الأزمات مما ينعكس على الصحة النفسية للطلاب في مرحلة التعليم الجامعي
Researcher aimed to detect the relationship between Psychological Immunity and its Relation with Anxiety & Hypochondria Caused by Coronavirus Covied - 19 for a sample consisted of (465) students from some Universities in Egypt, differences between average scores of the University Students in Anxiety & Hypochondria that are attributable to Gender (Male - Female), that Are attributable to Social Environment (urban-rural).Result: There Are statically significant relationship between Psychological Immunity both Anxiety & Hypochondria, There are statistically significant differences between Averages score of the university students in Anxiety & Hypochondria are attributable to Gender (Male-Female), and there are no statistically significant differences between Averages score of the university students in Anxiety & Hypochondria are attributable to Social Environment (Urban-Rural).The researcher extracts from the results of the current research the importance of developing psychological immunity to support him in crisis situations, which is reflected on the mental health of students in the stage of university education
Keywords: فيروس كورونا "كوفيد-19" -- الأمراض المعدية -- الصحة النفسية -- الاضطرابات النفسية -- طلبة الجامعات